2022
DOI: 10.21203/rs.3.rs-1957161/v1
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

WITHDRAWN: Global metabolic changes by Bacillus cyclic lipopeptide extracts on stress responses of para rubber leaf

Abstract: The changing environmental conditions generate the abiotic stress like exposing of chemicals and biotic stress like Phytophthora palmivora infection which is causes leaf fall disease affecting the growth rate of para rubber seedlings resulting in economic loss. To prevent abiotic and biotic stresses, biocontrol agents like cyclic lipopeptides (CLPs) from Bacillus spp. have been introduced to reduce the usage of chemically synthesized fungicides and fertilizers. This study aimed to use Bacillus CLP extracts as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…In addition, cyclic lipopeptides from Bacillus spp. have been introduced to prevent abiotic and biotic stresses and promote plant growth (Tunsagool et al, 2023). The evidence suggested that Ornithinibacillus is associated with ammonium nitrogen and plays a regulatory role in the nitrification process during composting (Zhai et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, cyclic lipopeptides from Bacillus spp. have been introduced to prevent abiotic and biotic stresses and promote plant growth (Tunsagool et al, 2023). The evidence suggested that Ornithinibacillus is associated with ammonium nitrogen and plays a regulatory role in the nitrification process during composting (Zhai et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Metabolite extraction followed a previously established procedure (Tunsagool et al, 2023). In short, 15 mg of fine powder was weighed and combined with 1 mL of a solution composed of methanol, water, and chloroform in a ratio of 2.5:1:1 (v/v/v).…”
Section: Metabolite Extractionmentioning
confidence: 99%
“…Metabolomics, a potent analytical method, enables the comprehensive study of small molecules in biological systems (Hajjar et al, 2023), particularly healthbeneficial molecules. It has been used for untargeted metabolomics to elucidate metabolite alterations in various parts of plants, such as leaves (Ibrahim et al, 2023;Tunsagool et al, 2023). Metabolomics revealed the metabolite profile with altered levels of primary and secondary metabolites belonging to various classes, especially in green plants (Kumar et al, 2023a(Kumar et al, , 2023b linking to functional benefit prediction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations